(untitled) (Research, Society and Development, 2021)
This work describes the bioprospection and characterization of cellulase-producing bacteria isolated from the soil obtained in a preserved region of the Cerrado biome, in Uberaba, Brazil. Cellulolytic activity was confirmed in 14 of the 84 bacterial strains isolated. According to enzymatic quantification, five strains were selected as the best cellulase producers, and based on the partial sequencing of the 16S rRNA gene the strains were identified as Bacillus siamensis (isolate AB-9;5.000U/mL), Bacillus toyonensis (isolate AB-1;4.630U/mL), Bacillus methylotrophicus (isolates MB-3;4.236U/mL and MP-7;4.282U/mL), and Bacillus drentensis (isolate ME-2;4.444U/mL). The enzymatic extract obtained from B. siamensis AB-9 was the most stable in different pH values (2-8), maintaining its cellulolytic activity, while B. toyonensis AB-1 and B. methylotrophicus MP-7 produced cellulases with maximum activity at pH 7 and 8. The cellulases produced by B. siamensis AB-9 and B. toyonensis AB-1 showed high enzymatic activity at all temperatures analyzed (10-80°C), while B. methylotrophicus MB-3 cellulases had maximum activity in the range of 20-70°C. To our knowledge, this is the first time that cellulase-producing bacteria isolated from Brazilian Cerrado biome in the region of Triângulo Mineiro with potential biotechnological application are described.